Piezoelectric composite films for real-time foot strike detection and energy generation - Panpho, Phakakorn; Charoonsuk, Thitirat; Vittayakorn, Naratip; Charoenthai, Nipaphat; Bongkarn, Theerachai; Sumang, Rattiphorn (My University, 2025)
Energy harvesting technology integrated into running shoes enables the conversion of mechanical energy from foot strikes into electrical signals for real-time monitoring. This approach enhances running efficiency, reduces injury risk, and eliminates the need for external power sources. In this study, composite films combining lead-free piezoelectric ceramics (KNNS-BNZ-xBF) with PDMS were developed for efficient energy harvesting and accurate detection of foot-strike patterns. XRD analysis revealed a broad R–O–T phase coexistence zone (0 ≤ x ≤ 0.006) and a transition to an R–T phase boundary for x > 0.006, with reduced grain size as xBF increased. The sample with xBF = 0.006 mol.% showed optimal electrical properties and was selected for composite film fabrication. Electrical output increased with ceramic loading, reaching maximum open-circuit voltage (VOC) and short-circuit current (ISC) at 18 wt% KBB due to enhanced piezoelectric response and uniform particle dispersion. The films, mounted on running shoe soles, successfully detected different foot-strike patterns (heel strike, midfoot, and forefoot). This system demonstrates strong potential for wearable sensors in athletic monitoring and injury prevention.
Keywords: Energy harvesting; Foot-strike detection; KNNS-BNZ-xBF; Piezoelectric; Running shoe sensor